Improving the Effectiveness of Training for the Creation of Simple and Effective Corn Fertilizer Tools Through the Use of Innovative Video Tutorials - kusnanto kusnanto; Mira Mira; Candra Gudianto (Institut Teknologi Nasional, Bandung, 2023)
In Desa Puteng, an agricultural village within Bengkayang Regency, corn cultivation plays a significant role in the local economy. However, farmers in this community often encounter challenges in effectively fertilizing their corn crops, resulting in diminished productivity. To address this issue, an innovative approach to enhance training for the creation of simple and effective corn fertilizer tools was introduced through the use of video tutorials, which helped overcome language barriers, and offered visual, step-by-step guidance. This approach is aimed at improving the effectiveness of training and ensuring that farmers can easily access knowledge and skills, thereby increasing their agricultural productivity. Moreover, it also has the potential to disseminate agricultural information and technology to remote farming communities, contributing to the overall agricultural development in the region. This project was initiated by Institut Shanti Bhuana, with the primary goal of empowering the local corn farming community through effective training in corn fertilizer tool construction using innovative video tutorials. The objectives were to enhance farmers' understanding on efficient corn fertilization, teach them simple yet effective tool-making techniques, and overcome language barriers. Through the implementation of this project, Institut Shanti Bhuana aspires to create a positive impact on farmers' lives and elevate the overall welfare of rural communities.